Effect of Different Energy to Protein Ratio and Tallow Supplementation on Broiler Performance - Sadeghi, GH.; Tabiedian, S.A. (International Journal of Poultry Science, 2005)
This experiment was carried out to examine the effect of tallow supplementation and reducing protein level on broiler chickens performance. A total of 480 one-day old broiler chicks of a commercial strain (Arian) from both sex with equal ratio were placed in 32 pens, fifteen in each pen. Treatments were included tallow at 0, 2.5, 5 and 7.5% levels and protein level reduction in NRC energy diets as ME to CP ratio increased 10 unit. Each treatment replicated four times. Metabolizable energy of tallow was determined by Sibbald method. Results showed that AMEn value of tallow was 7150 kcal kg-1. In whole production period (days 7-56) chicks that fed with a diet containing NRC protein level, adding 5 and 7.5 percent tallow significantly (P< 0.05) increased feed intake but in reduced protein diets, adding tallow could not affect feed intake. Feeding different levels of tallow and diet protein reduction in both low and high energy diets had no significant effect on weight gain in ages 1-21 and 42-56 and 7-56. There was no significant difference in feed conversion ratio in chicks fed with different experimental diets in all ages. Carcass, liver and abdominal fat did not affect by experimental treatments. The results showed that adding 2.5 percent tallow to a diet with a protein level according to NRC recommendation results to better performance.